Militarism and Industry. - Perlo, Victor (New York US: International Publishers, 1963)
Trata acerca del crecimiento de la industria y negocio militar.
Keywords: MILITARISMO; ARMAS; ARMAMENTISMO; GUERRA; FUERZAS ARMADAS; INDUSTRIA